Assessment of nutritional status of children aged under five years in tribal population of Jawadhu hills in Tamil Nadu - T. T., Gopinath; Logaraj, M.; John, K. R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Malnutrition is more common in India than in Sub-Saharan Africa. One in every three malnourished children in the world lives in India. Tribal population constitutes about 8% of the total population in India. They are particularly vulnerable to under nutrition, because of their geographical isolation, socio-economic disadvantage and inadequate health facilities. The objectives of this study were to assess the Nutritional status of children under five years in a Tribal area of Jawadhu hills under Puthurnadu PHC Sub-center and to find the associated risk factors accompanying the under five children. Methods: A community based cross sectional study was conducted in a tribal area of Jawadhu hills Puthurnadu PHC sub-center. A total of 316 children participated in the study. A predesigned, pre tested questionnaire was used to collect data on socio demographic profile (age, sex, religion, education, income) from the Mother/Guardian and measured all possible anthropometric measurements. Results: The overall prevalence of under nutrition was 26.9% in which Severely under nourished were 9.2%, the overall prevalence of stunting was 55.4% in which severely stunted were 23.4% and the overall prevalence of wasting was 10.4% in which severely wasted were 1.9% respectively. Male children were found to be more malnourished than Female children in our study. Children from joint family are more prone to get malnourished than Nuclear families. Conclusions: The overall prevalence of stunting was higher (55.4%) which is greater than the cut-off point stated by the World Health Organization to indicate that the severity of malnutrition. Adequate measures to be made to overcome malnutrition.